Impact of daily diet on military training injuries among high-altitude officers and soldiers - DONG Yutong; YANG Maolin; ZHANG Yangkai (陆军军医大学学报)
Objective‍　‍To explore the characteristics of military training injuries in high-altitude troops and determine the possible impact of daily diet on these training injuries in order to provide theoretical reference for scientific training and medical service support for high-altitude troops. Methods‍　‍A cross-sectional scheme was adopted in this study. A self-designed Military Training Injury Questionnaire for Plateau Troops was used to survey the officers and soldiers from resident high-altitude troops in July 2024 for their training injuries， daily diet， and other situations. The obtained data were statistically analyzed. Results‍　‍Among the 3 655 participants， the incidence of military training injuries was 17.87%. The subject with highest incidence was physical training （45.94%）， the most common season was winter （31.39%）. The most common sites of injury were waist （28.48%）， knees （22.21%）， and ankles （18.07%）， and the most common types were sprains （28.48%）， chronic fatigue injuries （18.38%） and strains （12.25%）. The intake amounts of coarse grains and potatoes， bean products， aquatic products and nuts were relatively low in the daily diet of high-altitude troops. Multivariate logistic regression analysis found intake of fruit （OR=0.625， 95%CI： 0.508~0.768， P<0.001） and of nut （OR=0.759， 95%CI： 0.654~0.879， P<0.001） were correlated with the occurrence of training injury. Conclusion‍　‍The occurrence pattern of military training injuries in high-altitude troops in this survey is basically consistent with that of previous reports， but the incidence rate is slightly decreased. Regular consumption of fruit and nut may be protective factors for the occurrence of training injuries.